2018
DOI: 10.1186/s13104-018-3706-x
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of anemia and associated factors among pregnant women attending public institutions of Shire Town, Shire, Tigray, Northern Ethiopia, 2018

Abstract: ObjectiveAnemia is a widespread health problem among pregnant women causing maternal/infant morbidity and mortality mainly in low-income countries. Understanding of the magnitude of anemia and related socio-demographic variables in a specific setting would help scale-up preventive and therapeutic measures in a locality. So that this study focuses on the magnitude of anemia and its associated factor among pregnant women attending antenatal care in public hospitals of shire town and using institution based cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
6
10
0
Order By: Relevance
“…Pregnant women's birth interval having less than two years [AOR (95% CI) = 2.87 (1.51 -5.44), P = 0.001] were 2.87 times more likely to be anemic compared to those with birth interval more than two years. This study finding is also found similar with other studies conducted in at Northern Ethiopia [4], Addis Ababa Ethiopia [32], and Arba Minch Town, Ethiopia [26]. The birth interval less than two years might be associated with a decreased iron store of women due to increase the incidence of anemia in pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Pregnant women's birth interval having less than two years [AOR (95% CI) = 2.87 (1.51 -5.44), P = 0.001] were 2.87 times more likely to be anemic compared to those with birth interval more than two years. This study finding is also found similar with other studies conducted in at Northern Ethiopia [4], Addis Ababa Ethiopia [32], and Arba Minch Town, Ethiopia [26]. The birth interval less than two years might be associated with a decreased iron store of women due to increase the incidence of anemia in pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Pregnant women having parasitic infestation were nearly 12 times AOR= 11.886(95% CI 5.606, 25.204) more likely to be anemic than their counterparts. This finding is consistent with studies conducted in Gondar (25), Shire (12), Adigrat (24), and North Shoa (9). This might be due to the reason that parasites attach and injure upper intestinal mucosa and ingest blood.…”
Section: Discussionsupporting
confidence: 91%
“…By investigating the prevalence of anaemia over 11 years, analysing its determinants and inequalities, the results of this study provide a comprehensive overview of the serious public health concern of anaemia among Ethiopian children aged 6–23 months. Previous studies investigated specific determinants, isolated geographical patterns and distinct time‐points of anaemia in Ethiopia (Abebe et al, 2018; Desalegn et al, 2014; Ejigu et al, 2018; Kebede, Gerensea, Amare, Tesfay, & Teklay, 2018; Reithinger et al, 2013). This study offers essential insights on top of these findings.…”
Section: Discussionmentioning
confidence: 99%